Differences in brain responses between lean and obese women to a sweetened drink. Issue 7 (9th April 2013) - Connolly, L.; Coveleskie, K.; Kilpatrick, L. A.; Labus, J. S.; Ebrat, B.; Stains, J.; Jiang, Z.; Tillisch, K.; Raybould, H. E.; Mayer, E. A.
Abstract Background Ingestion of sweet food is driven by central reward circuits and restrained by endocrine and neurocrine satiety signals. The specific influence of sucrose intake on central affective and reward circuitry and alterations of these mechanisms in the obese are incompletely understood. For this, we hypothesized that (i) similar brain regions are engaged by the stimulation of sweet taste receptors by sucrose and by non‐nutrient sweeteners and (ii) during visual food‐related cues, obese subjects show greater brain responses to sucrose compared with lean controls. Methods In a double‐blind, crossover design, 10 obese and 10 lean healthy females received a sucrose or a non‐nutrient sweetened beverage prior to viewing food or neutral images. BOLD signal was measured using a 1.5 Tesla MRI scanner. Key Results Viewing food images after ingestion of either drink was associated with engagement of similar brain regions (amygdala, hippocampus, thalamus, anterior insula). Obese differed from lean subjects in behavioral and brain responses rating both beverages as less tasteful and satisfying, yet demonstrating greater brain responses. Obese subjects also showed engagement of an additional brain network (including anterior insula, anterior cingulate, hippocampus, and amygdala) only after sucrose ingestion. Conclusions & Inferences Obese subjects had a reduced behavioral hedonic response, yet a greater engagement of affective brain networks, particularly after sucrose ingestion, suggesting that in obese subjects, lingual and gut‐derived signaling generate less central hedonic effects than food‐related memories in response to visual cues, analogous to response patterns implicated in food addiction.